2014
DOI: 10.1016/j.bbamem.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Lo/Ld phase coexistence modulation induced by GM1

Abstract: Lipid rafts are assumed to undergo biologically important size-modulations from nanorafts to microrafts. Due to the complexity of cellular membranes, model systems become important tools, especially for the investigation of the factors affecting "raft-like" Lo domain size and the search for Lo nanodomains as precursors in Lo microdomain formation. Because lipid compositional change is the primary mechanism by which a cell can alter membrane phase behavior, we studied the effect of the ganglioside GM1 concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 74 publications
6
39
0
Order By: Relevance
“…Although accurate in detecting and measuring the size of pre-existing nanodomains, these methods are not fast enough to follow the generation of nanodomains. Therefore, we decided to use indirect approaches such as fluorescence quenching [22,46] or Forster Resonant Energy Transfer (FRET) [27]. FRET or self-quenching occurs when two (similar or different) fluorescent molecules are found together within a 3 to 10 nm radius.…”
Section: Introductionmentioning
confidence: 99%
“…Although accurate in detecting and measuring the size of pre-existing nanodomains, these methods are not fast enough to follow the generation of nanodomains. Therefore, we decided to use indirect approaches such as fluorescence quenching [22,46] or Forster Resonant Energy Transfer (FRET) [27]. FRET or self-quenching occurs when two (similar or different) fluorescent molecules are found together within a 3 to 10 nm radius.…”
Section: Introductionmentioning
confidence: 99%
“…Although accurate in detecting and measuring the size of pre-existing nanodomains, direct imaging is not fast enough to follow the generation of nanodomains. Therefore, we decided to use indirect approaches such as fluorescence quenching2425 or Forster Resonant Energy Transfer (FRET)26. FRET or self-quenching occurs when two (similar or different) fluorescent molecules are found together within a 3 to 10 nm radius.…”
mentioning
confidence: 99%
“…Moreover, Allo uptake shifts the relative distribution in favor of the L d phase [30]. It is interesting to note that other studies found that the insertion of exogenous molecules in lipid bilayers in the L o + L d coexistence region leads to a modification of the relative proportions of the two liquid phases [37,38]. In addition, the shift amount depends on the lipid bilayer patch under observation.…”
Section: Resultsmentioning
confidence: 95%
“…2 to help discussion and interpretation of our data. On the basis of the reported phase diagram, at room temperature, the particular composition that we chose should be inside the two-phase coexistence region but very near to the miscibility border through a critical point [37]. Moreover, considering the phase diagram with fixed 1:1 DOPC\bSM ratio as a function of cholesterol content and focussing on the high cholesterol concentration region, where the 1:1:1 mixture is to be positioned, the miscibility border as a function of cholesterol concentration is very steep [35].…”
Section: Resultsmentioning
confidence: 99%